The Middle Paleolithic Percussion or Pressure Flaking Tools? The comparison of experimental and archaeological material from Croatia - Karavanić, Ivor (Array, 2003)
A lithic knapping experiment was done to establish the morphology of the marks which appeared on bone retouchers (flaking tools) and to explore differences arising from the use of bone retouchers using both percussion and pressure. The morphological characteristics of the marks on retouchers caused by percussion flaking and those caused by pressure flaking have been established. The comparison of experimental and archaeological material seems to suggest the presence of both techniques in the Mousterian of north-western Croatia. Based on this evidence the authors believe that the Neanderthals were capable of retouching their tools by using both percussion and pressure techniques, although the results of this experiment are not enough to prove that they actually did so. However, the morphology of marks made by pressure flaking is not uniform and the similar marks may derive from some other activity.